Cryo-EM Visualization of Lipid and Polymer-Stabilized Perfluorocarbon Gas Nanobubbles - A Step Towards Nanobubble Mediated Drug Delivery. Issue 1 (December 2017) - Hernandez, Christopher; Gulati, Sahil; Fioravanti, Gabriella; Stewart, Phoebe; Exner, Agata
Abstract Gas microbubbles stabilized with lipids, surfactants, proteins and/or polymers are widely used clinically as ultrasound contrast agents. Because of their large 1–10 µm size, applications of microbubbles are confined to the blood vessels. Accordingly, there is much interest in generating nanoscale echogenic bubbles (nanobubbles), which can enable new uses of ultrasound contrast agents in molecular imaging and drug delivery, particularly for cancer applications. While the interactions of microbubbles with ultrasound have been widely investigated, little is known about the activity of nanobubbles under ultrasound exposure. In this work, we demonstrate that cryo-electron microscopy (cryo-EM) can be used to image nanoscale lipid and polymer-stabilized perfluorocarbon gas bubbles before and after their destruction with high intensity ultrasound. In addition, cryo-EM can be used to observe electron-beam induced dissipation of nanobubble encapsulated perfluorocarbon gas.